Identification of Pests and Diseases in Atlantic Variety of Potato (Solanum Tuberosum) Crops in Sukapura Village Kertasari District Bandung District - Muhammad, Irfan; Sidik, Ihsan Maulana (Society : Jurnal Pengabdian Masyarakat, 2025)
Potatoes are plants that grow in highland areas. Potatoes have the potential to be exported to various countries because they are used as a source of carbohydrates. The purpose of this technical note is to provide information on the identification of pests and diseases that attack the Atlantic variety of potato (Solanum tuberosum) in Sukapura Village.  Field Work Practice activities were carried out on June 3 - July 20, 2024 at Sumber Jaya, Sukapura Village, Kertasari District, Bandung Regency. The method used to obtain primary data is direct observation and interviews with field supervisors. The method used to obtain secondary data by means of literature studies. The results of observations have revealed a variety of pests and diseases in potato plants, which are controlled by applying pesticides for control. The results of this control obtained suppression of the intensity of pest attacks on potato plants (Solanum tuberosum) Atlantic varieties.